How is research policy across the OECD organised? Insights from a new policy database - Borowiecki, Martin (OECD Science, Technology and Industry Policy Papers, 2018)
Building on a newly created policy indicator database, this paper provides a first systematic comparison of the governance of public research policy across 35 OECD countries from 2005 to 2017. The database was obtained following a three-year process that involved the development of an ontology of the governance of public research policy as well as data collection and validation by national authorities. The data show diverse institutions and mechanisms of policy action regarding higher education institutions (HEIs) and public research institutes (PRIs) are in place across the 35 OECD countries. The data also shows an increasing use of project funding, performance contracts and performance evaluations for HEIs and PRIs. In many countries, HEIs and PRIs are autonomous regarding their relations with industry, budget allocation but less frequently regarding salaries. Recent reforms have strengthened external stakeholders' participation in their governance. The database is publicly available on the following webpage: https://stip.oecd.org/resgov